(untitled) - Stephen Gasiorowicz (Englewood Cliffs, New Jersey, 1993)
The book treats physics from Galileo to the late nineteenth century as "classical" and most of the developments in physics from the late nineteenth century to the present as "modern". Examples representing typical problems are numerous throughout. Their solutions illustrate sound approaches to problem-solving. At the end of each chapter are problems, totaling 2500, and thought questions, totaling about 700. There are also general problems, which bring together material from the entire chapter as well as from previous chapters. The problems are labeled I, II, III. Level I problems are "easy". Level II problems are typically multistep and reiquire an increased understanding for the interconnectedness of physics. Level III problems are specially challenging, in some case demanding significant synthesis of concepts in the text
Keywords: physics